The Influence of Flipped Classroom Learning Strategies in Improving Ability in Understanding Mathematics Concepts Statistic Materials in Grade VIII at SMP 1 Baturaden - Fenita Riyanti; Amel Zitouni (International Journal of Research in Mathematics Education, 2023)
The ability to understand concepts is very important to understand learning material in the framework of learning outcomes that are in accordance with the goals to be achieved. The low understanding of students is caused by two factors, namely internal factors and external factors. Internal factors are factors from within while external factors are factors that are outside the individual. The selection of learning strategies is an external factor that can increase students' understanding. Learning methods are less innovative and boring, such as only listening to teacher explanations and lack of student activity in learning, and are still teacher-centered and students often feel bored with ongoing learning. This type of research uses an experimental method. The population in this study was class VIII at SMP Negeri 1 Baturaden. The sample of this research is class VIII A and VIII B which consist of 66 students. Analysis using the t test. Conceptual understanding is an important aspect of learning that allows students to acquire in-depth and sustainable knowledge. In recent years, the Flipped classroom learning strategy has emerged as an innovative approach in education, in which learning materials are conveyed to students outside the classroom through videos or reading materials, while class time is used for discussion and application of concepts. This study aims to determine the effect of the strategy